Cervical Spine Alignment in the Sagittal Axis: A Review of the Best Validated Measures in Clinical Practice. Issue 8 (October 2021) - Martini, Michael L.; Neifert, Sean N.; Chapman, Emily K.; Mroz, Thomas E.; Rasouli, Jonathan J.
Study Design: Review of the best-validated measures of cervical spine alignment in the sagittal axis. Objective: Describe the C2-C7 Cobb Angle, C2-C7 sagittal vertical axis, chin-brow to vertical angle, T1 slope minus C2-C7 lordosis, C2 slope, and different types of cervical kyphosis. Methods: Search PubMed for recent technical literature on radiograph-based measurements of the cervical spine. Results: Despite the continuing use of measures developed many years ago such as the C2-C7 Cobb angle, there are new radiographic parameters being published and utilized in recent years, including the C2 slope. Further research is needed to compare older and newer measures for cross-validation. Utilizing these measures to determine the degree of correction intraoperatively and postoperatively will enable surgeons to optimize patient-level outcomes. Conclusion: Cervical spinal deformity can be a debilitating condition characterized by cervical spinal misalignment that affects the elderly more commonly than young populations. Many of these validated measures of cervical spinal alignment are useful in clinical settings due to their ease of implementation and correlations with various postoperative and health-related quality of life outcomes.